Advances in nano-based materials for glioblastoma multiforme diagnosis: A mini-review - Luiza Araújo Gusmão; Flávia Sayuri Matsuo; Hellen Franciane Gonçalves Barbosa; Antonio Claudio Tedesco (Frontiers in Nanotechnology, 2022)
The development of nano-based materials for diagnosis enables a more precise prognosis and results. Inorganic, organic, or hybrid nanoparticles using nanomaterials, such as quantum dots, extracellular vesicle systems, and others, with different molecular compositions, have been extensively explored as a better strategy to overcome the blood-brain barrier and target brain tissue and tumors. Glioblastoma multiforme (GBM) is the most common and aggressive primary tumor of the central nervous system, with a short, established prognosis. The delay in early detection is considered a key challenge in designing a precise and efficient treatment with the most encouraging prognosis. Therefore, the present mini-review focuses on discussing distinct strategies presented recently in the literature regarding nanostructures’ use, design, and application for GBM diagnosis.